Practical Boat Mechanics : Commonsense Ways to Prevent, Diagnose, and Repair Engine and Mechanical Problems - Evridge, Ben L. (Camden, ME International Marine, 2009)
Work-around solutions and emergency repairs that will get your boat home when all else fails.
Include Figures, Illustrations, Tables and Index.
Commonsense Ways to Prevent, Diagnose, and Repair Engine and Mechanical Problems.
Keywords: Motorboats--Motors--Maintenance and repair -- Boats and boating--Maintenance and repair